Expanding the speech and language phenotype in Koolen-de Vries syndrome: late onset and periodic stuttering a novel feature - St John, Miya; van Reyk, Olivia; Koolen, David A.; de Vries, Bert B. A.; Amor, David J.; Morgan, Angela T. (European journal of human genetics : EJHG, 2023)
Speech and language impairment is core in Koolen-de Vries syndrome (KdVS), yet only one study has examined this empirically. Here we define speech, language, and functional/adaptive behaviour in KdVS; while deeply characterising the medical/neurodevelopmental phenotype in the largest cohort to date. Speech, language, literacy, and social skills were assessed using standardised measures, alongside an in-depth health and medical questionnaire. 81 individuals with KdVS were recruited (35 female, mean age 9y 10mo), 56 of whom harboured the typical 500-650 kb 17q21.31 deletion. The core medical phenotype was intellectual disability (largely moderate), eye anomalies/vision disturbances, structural brain anomalies, dental problems, sleep disturbance, musculoskeletal abnormalities, and cardiac defects. Most were verbal (62/81, 76.5%), while minimally-verbal communicators used alternative and augmentative communication (AAC) successfully in spite of speech production delays. Speech was characterised by apraxia (39/61, 63.9%) and dysarthria (28/61, 45.9%) in verbal participants. Stuttering was described in 36/47 (76.6%) verbal participants and followed a unique trajectory of late onset and fluctuating presence. Receptive and expressive language abilities were commensurate with one another, but literacy skills remained a relative weakness. Social competence, successful behavioural/emotional control, and coping skills were areas of relative strength, while communication difficulties impacted daily living skills as an area of comparative difficulty. Notably, KdVS individuals make communication gains beyond childhood and should continue to access targeted therapies throughout development, including early AAC implementation, motor speech therapy, language/literacy intervention, as well as strategies implemented to successfully navigate activities of daily living that rely on effective communication.